TNAP—a potential cytokine in the cerebral inflammation in spastic cerebral palsy - Wang, Xiao-Kun; Gao, Chao; Zhong, He-Quan; Kong, Xiang-Yu; Qiao, Rui; Zhang, Hui-Chun; Chen, Bai-Yun; Gao, Yang; Li, Bing (Frontiers in Molecular Neuroscience, 2022)
OBJECTIVE. Several studies have shown the significance of neuroinflammation in the pathophysiological development of cerebral palsy (CP). However, the etiology of CP remains poorly understood. Spastic CP is the most common form of CP, comprising 80% of all cases. Therefore, identifying the specific factors may serve to understand the etiology of spastic CP. Our research was aimed to find some relevant factors through protein profiling screening and validation to help understand the pathogenesis of cerebral palsy. MATERIALS AND METHODS. In the current study, related clinical parameters were assessed in 18 children with spastic CP along with 20 healthy individuals of the same age. Blood samples of the spastic CP children and controls were analyzed with proteomics profiling to detect differentially expressed proteins. On the other hand, after hypoxic ischemic encephalopathy (HIE) was induced in the postnatal day 7 rat pups, behavioral tests were performed followed by detection of the differentially expressed markers and inflammatory cytokines in the peripheral blood and cerebral cortex of the CP model rats by ELISA and Western blot. Independent sample t-tests, one-way analysis of variance and the Pearson correlation were used for statistical analysis. RESULTS. Through proteomic analysis, differentially expressed proteins were identified. Among them, TNAP, the gene expression product of ALPL, was downregulated in spastic CP. In addition, significantly lower TNAP levels were found in the children with CP and model rats. In contrast, compared with the sham rats, the model rats demonstrated a significant increase in osteopontin and proinflammatory biomarkers in both the plasma and cerebral cortex on the ischemic side whereas serum 25 hydroxyvitamin D and IL-10 were significantly decreased. Moreover, serum TNAP level was proved to be positively correlated with serum CRP and IL-10 in model rats. CONCLUSION. These results suggest that TNAP is the potential molecule playing the specific and critical role in the neuroinflammation in spastic CP, which may provide promising target for diagonosis and treatment of spastic CP.